1998
DOI: 10.1021/ja973325x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Non-Peptide Somatostatin Agonist with SST4 Selectivity

Abstract: The discovery of novel non-peptide compounds with a high affinity for the peptide hormone somatostatin (SST) receptor is described. The compounds were tested for affinity at five human SST receptor subtypes individually expressed in mammalian cells. The compound NNC 26-9100 showed a K i of 6 nM at SST 4 and more than 100 fold selectivity for SST 4 over SST 1 , SST 2 , SST 3 , or SST 5 . Competition binding studies and Scatchard analysis of the interaction by NNC 26-9100 with SST showed specificity at SST 4 . F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 17 publications
0
55
0
Order By: Relevance
“…A.M. Crider per previously established protocols (Ankersen et al, 1998; Crider et al, 2004). All other chemicals and reagents, unless otherwise stated, were purchased from Sigma-Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A.M. Crider per previously established protocols (Ankersen et al, 1998; Crider et al, 2004). All other chemicals and reagents, unless otherwise stated, were purchased from Sigma-Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…Not only are the cortex and hippocampus areas vital to learning and memory, but are also significantly affected by Aβ accumulation and associated with reduced neprilysin levels in Alzheimer’s disease patients (Yasojima et al, 2001a; Yasojima et al, 2001b). The SSTR4 agonist NNC 26-9100 is an enzymatically stable non-peptide drug having a >100-fold selectivity for SSTR4 over other subtypes (Ankersen et al, 1998; Crider et al, 2004). We have previously shown that chronic (i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…1) is a highly selective and high affinity sst4 receptor agonist, with >100-fold selectivity for sst4 over all other somatostatin receptor subtypes (K i = 6 nM) (Ankersen et al, 1998; Crider et al, 2004). To determine the ability of NNC 26-9100 to appropriately distribute to the brain we assessed brain uptake of radioactively labeled NNC 26-9100 via jugular vein injection (mouse), as well as regional distribution to critical brain areas associated with Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, smallmolecule agonists have been described, even for receptors for larger hormones like insulin, TPO, and EPO (18)(19)(20), but none of these receptors belong to the GPCR superfamily. Within the GPCRs, small-molecule agonists have been described, e.g., for the arginine vasopressin V-2 receptor, the somatostatin receptor, the bradykinin receptor, the cholecystokinin receptor, the angiotensin II receptor, and the growth hormone secretagogue receptor (21)(22)(23)(24)(25)(26). However, none of these GPCRs belong to the B family, and the natural ligands are all either fairly small or have a defined secondary structure.…”
mentioning
confidence: 99%